Two new species of cichlid fish genus Geophagus Heckel from the Rio Tocantins drainage (Perciformes: Cichlidae) - Lucinda, Paulo H. F.; Lucena, Carlos A. S.; Assis, Newton C. (Zootaxa, 2010)
Geophagus sveni n. sp. and G. neambi n. sp. are described from the Rio Tocantins drainage of Brazil. Geophagus sveni and G. neambi differ from some of its congeners by the lack of head markings. G. sveni is distinguished from the species lacking head markings by the presence of five faint undivided vertical bars, proeminent mid-lateral blotch, and by the caudal fin vertically clear and black barred; G. neambi differs from the species lacking head markings by the possession of eight or nine vertical, parallel bars along the flank, the bar containing mid-lateral spot bifurcate above and below midlateral blotch and by the caudal fin bearing rounded white spots. Geophagus sveni differs from the sympatric and syntopic Geophagus neambi by the presence of five faint vertically bars (vs. eight or nine conspicuous dorso-ventral bifurcated vertically bars).